Effects of Different Carbohydrate Levels in Diets on Growth Performance and Muscle Nutritive Value of Ying Carp and Scattered-Scaled Mirror Carp (Cyprinus carpio) - Pengfei Xiao; Yunya Wu; Hang Sha; Xiangzhong Luo; Guiwei Zou; Hongwei Liang (Aquaculture Nutrition)
This experiment aimed to assess the dietary adaptation and utilization of high carbohydrate diets to Ying carp and scattered-scaled mirror carp (Cyprinus carpio), focusing on growth performance, muscle nutritive value, and nutrient metabolism. Ying carp (4.5 ± 0.2 g) and scattered-scaled mirror carp (5.01 ± 0.2 g) were fed isonitrogenous diets containing 20%, 30%, and 40% carbohydrates for 8 weeks; the nitrogen content of the three feeds was (5.12% ± 0.03%). After the trail, the final body weight, feed efficiency, and specific growth rate of both carp varieties were analyzed. Results showed that the final body weight, feed efficiency, and specific growth rate of both carp varieties were significantly higher at the 30% carbohydrate level compared to 20% and 40%, indicating improved growth performance (p<0.05). Crude protein content in whole fish composition was significantly higher at the 30% carbohydrate level compared to the other two levels (p<0.05) for both varieties. However, excessive carbohydrate intake (40%) led to pronounced liver fat deposition in both varieties, with scattered-scaled mirror carp showing less severe deposition than Ying carp. As the carbohydrate levels in the feed increased, the essential amino acid (EAA) and total amino acid (TAA) content in the muscle of both carp varieties significantly increased, while the content of unsaturated fatty acids in the muscle significantly decreased (p<0.05). Gene expression analysis revealed enhanced glycolytic activity (pk1) and inhibited gluconeogenesis (g6p and pepck) in the liver with higher carbohydrate levels. In muscle tissue, high carbohydrate diets reduced expression levels of genes involved in polyunsaturated fatty acid (PUFA) synthesis (elovl5, elovl6, and rxrgb). The two carp varieties exhibited distinct adaptations to varying dietary carbohydrate levels. While a 30% carbohydrate diet enhanced the growth performance of both varieties, scattered-scaled mirror carp demonstrated higher growth efficiency, whereas Ying carp excelled in maintaining muscle nutrient quality, particularly regarding PUFAs and amino acid composition. These findings suggest that carbohydrate levels in feed should be optimized based on the specific goals of aquaculture, whether prioritizing rapid growth or improved muscle nutrition. Moreover, variations in the expression of genes related to carbohydrate metabolism between the two varieties influenced their metabolic responses, offering insights for designing variety-specific feeding strategies to support sustainable aquaculture practices.